2011
DOI: 10.1111/j.1872-034x.2011.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver regeneration is promoted by increasing serotonin content in rat liver with secondary biliary cirrhosis

Abstract: Our results showed that splenectomy promoted liver regeneration by increasing serotonin content in liver even under cirrhotic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…Accordingly, we observed significantly increased expression of major profibrogenic transcripts (eg, MMP2 , procollagen α1, TGF‐β1 , and α‐SMA ) that are strongly related to biliary fibrosis and nonanastomotic biliary stricture development . Moreover, ketanserin alleviated biliary fibrosis 4 weeks after the operation, as demonstrated by the reduction in collagen fibers and α‐SMA–positive MFs in the portal area as well as the down‐regulation of fibrosis‐related genes and HYP content in liver grafts.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Accordingly, we observed significantly increased expression of major profibrogenic transcripts (eg, MMP2 , procollagen α1, TGF‐β1 , and α‐SMA ) that are strongly related to biliary fibrosis and nonanastomotic biliary stricture development . Moreover, ketanserin alleviated biliary fibrosis 4 weeks after the operation, as demonstrated by the reduction in collagen fibers and α‐SMA–positive MFs in the portal area as well as the down‐regulation of fibrosis‐related genes and HYP content in liver grafts.…”
Section: Discussionmentioning
confidence: 75%
“…The secretion of TGF‐β1 was measured in PF culture supernatants with a rat TGF‐β1 enzyme‐linked immunosorbent assay kit (BioSource‐Invitrogen, Carlsbad, CA) according to the manufacturer's instructions. Serotonin levels in liver homogenates were also determined 1 day, 3 days, 1 week, 2 weeks, and 4 weeks after liver transplantation with a rat 5‐HT enzyme‐linked immunosorbent assay kit (IBL International, Hamburg, Germany) . Protein concentrations were determined according to the Bradford method with a protein assay kit (Bio‐Rad Laboratories, Inc., Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that splenectomy improves liver regeneration after PH [15e18]. The splenectomy affects platelet activation, portal blood flow, and oxygen supply [15,28,29]. Indeed, Ren et al [15] reported that splenectomy improved liver regeneration in the rat.…”
Section: 2mentioning
confidence: 97%
“…While similar findings after splenectomy have been reported [5,21], only a few reports have described changes in liver function tests during long-term follow up after splenectomy in patients with HCC and advanced cirrhosis. The causes of these improvements in liver function following splenectomy may be due to the following: a reduction in bilirubin overload by the removal of a huge spleen with damaged red blood cells [5], the removal of spleenderived inhibitors of liver regeneration, such as transforming growth factor-β1 [22], and the enhanced production of promoters for liver regeneration, such as platelet-derived serotonin [23]. It is also possible that the beneficial effects observed in the liver because of splenectomy may be due to IFN therapy.…”
Section: Discussionmentioning
confidence: 99%